2022
DOI: 10.3923/ajps.2022.192.202
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Micropropagation, Biological Activities and Phenolic Profile of Astragalus fruticosus Forssk

Abstract: Background and Objective: Astragalus fruticosus Forssk. is an endangered wild Egyptian plant, with a poor germination ratio and rich in valuable phytochemicals. This study was aimed to develop an efficient micropropagation protocol as well as a screening of the cytotoxic, antidiabetic activities and phenolic profile of the micropropagated plantlets. Materials and Methods: Murashige and Skoog (MS) medium fortified with different concentrations of N 6 -Benzyl Amino Purine (BAP), Kinetin (Kn) and thidiazuron (TDZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The study also identified the presence of luteolin and kaempferol flavonoids, pyrogallol, protocatechuic acid, p-coumaric acid, chlorogenic acid, ferulic acid and ellagic acid by comparing the high-performance liquid chromatography-ultraviolet (HPLC-UV) chromatograms of the plant's ethanolic extract and reference compounds. Astragalus fruticosus ethanolic extract showed α-glucosidase inhibitory activity (IC 50 = 44.8 µg/mL) and exhibited cytotoxic activity against breast (MCF-7) and leukemia (HL-60) cell lines (IC 50 of 28.3 µg/mL and 49 µg/mL, respectively) [34].…”
Section: Introductionmentioning
confidence: 99%
“…The study also identified the presence of luteolin and kaempferol flavonoids, pyrogallol, protocatechuic acid, p-coumaric acid, chlorogenic acid, ferulic acid and ellagic acid by comparing the high-performance liquid chromatography-ultraviolet (HPLC-UV) chromatograms of the plant's ethanolic extract and reference compounds. Astragalus fruticosus ethanolic extract showed α-glucosidase inhibitory activity (IC 50 = 44.8 µg/mL) and exhibited cytotoxic activity against breast (MCF-7) and leukemia (HL-60) cell lines (IC 50 of 28.3 µg/mL and 49 µg/mL, respectively) [34].…”
Section: Introductionmentioning
confidence: 99%